Analisis Waste Material pada Tulangan Kolom Berbasis Building Information Modeling (BIM) - Fernanda, Raka Aditya; Bayzoni, Bayzoni; Husni, Hasti Riakara; Ashruri, Ashruri (Universitas Lampung, 2023)
This research aims to investigate the influence of implementing BIM concepts on waste material analysis in type 1 and type 2 column reinforcement. Type 1 column reinforcement refers to the reinforcement applied on each floor separately, while type 2 column reinforcement refers to the reinforcement applied every two floors. In this research, the BIM concept is implemented using Autodesk Revit software. The research process begins with data collection, 3D structural modeling, reinforcement modeling, inputting reinforcement schedule marks, clash detection, outputting the Bar Bending Schedule (BBS), cutting lists, and waste material analysis. The research findings indicate that the total weight of type 1 column reinforcement requirement is 29319.17 kg for D16 and 10232.06 kg for Ø10, with a total weight of waste reinforcement is 2739.17 kg for D16 and 120.64 kg for Ø10. Meanwhile, the total weight of type 2 column reinforcement requirement is 32103.36 kg for D16 and 10232.06 kg for Ø10, with a total weight of waste reinforcement is 6350.03 kg for D16 and 120.64 kg for Ø10. The waste level of type 1 column reinforcement is 9.34% for D16 and 1.18% for Ø10, while the waste level of type 2 column reinforcement is 19.78% for D16 and 1.18% for Ø10. Based on the research findings, it can be concluded that type 1 column reinforcement is more effective and efficient compared to type 2 column reinforcement in terms of the weight requirement and waste generated.